FLIPPITY, an Innovative Educational Media Platform to Improve Students' English Speaking Fluency at SD MAN 1 TANJUNGBALAI - Morada Tetty; Julynar Putri Ayu Sitorus; Jessika Marsaulina Hasibuan; Hizkia Silaban; Muhammad Tapsir Hasibuan; Rosenna Siahaan (PT. Intelek Cendikiawan Nusantara, 2024)
This study explores the effectiveness of FLIPPITY, a web-based educational gamification platform, in improving English speaking fluency among elementary school students in Indonesia. English proficiency, particularly in speaking, is a significant challenge for students in non-English-speaking countries, including Indonesia, where English is not the primary language of instruction. The research focuses on students in grades 3 and 4 at SD MIN 1 Al-Iman, S.Dengki, Tanjungbalai, and examines how gamified content from FLIPPITY enhances student engagement, confidence, and speaking skills. The study employed a mixed-methods approach, incorporating pre- and post-tests, surveys, and observations to assess improvements in English speaking abilities. Findings indicate that students who engaged with FLIPPITY’s interactive activities, such as flashcards, quiz shows, and scavenger hunts, demonstrated significant progress in speaking fluency and expressed increased confidence in their English abilities. The study aligns with previous research by Richards and Renandya (2002) and Celce-Murcia and Olshtain (2000), which emphasize the importance of speaking proficiency in language learning. This research contributes to the growing body of literature on technology-assisted language learning, specifically highlighting the role of gamification in fostering language skills among young learners. The results suggest that FLIPPITY offers a promising tool for enhancing English speaking fluency and motivating students in the Indonesian context.